Analysis of the Defense of Insanity in International Criminal Law - Ajmal, Ali; Rasool, Faiza (Annals of Human and Social Sciences, 2024)
The objective of this study is to analyze the defense of insanity in international criminal law. The insanity defense is an affirmative defense. Article 31(1)(a) of the Rome Statute 2002 deals with the defense of insanity in international criminal law. The legal doctrinal analysis approach was adopted to study the defense of insanity in international criminal law. The findings suggest that insanity defense is allowed in the International Criminal Court and is dealt with likewise in most of the national jurisdictions across the world. The jurisprudence developed on the insanity defense in international criminal law reflects the important role of medical evidence and expert opinion in deciding the pleas of insanity. However, the criteria for the insanity defense given in 31(1)(a) of the Rome Statute 2002 need to be amended considering the latest developments in mental health and behavioral sciences.